Tax complexity in Australia: A survey-based comparison to the OECD average - Thomas Hoppe (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
This article comprehensively reviews Australia's corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia's tax framework, which covers processes and fea-tures such as tax law enactment or tax audits, is close to the OECD average. A more granular analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.
Keywords: H20; H25; C83; O57; 330; Tax Complexity; Corporate Income Tax System; Survey; Australia; OECD Countries